2010
DOI: 10.1186/1476-511x-9-64
|View full text |Cite
|
Sign up to set email alerts
|

Dietary red palm oil supplementation reduces myocardial infarct size in an isolated perfused rat heart model

Abstract: Background and AimsRecent studies have shown that dietary red palm oil (RPO) supplementation improves functional recovery following ischaemia/reperfusion in isolated hearts. The main aim of this study was to investigate the effects of dietary RPO supplementation on myocardial infarct size after ischaemia/reperfusion injury. The effects of dietary RPO supplementation on matrix metalloproteinase-2 (MMP2) activation and PKB/Akt phosphorylation were also investigated.Materials and methodsMale Wistar rats were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The activity of proteases in gel was detected using casein zymography (Bester et al, 2010). After electrophoresis, SDS-PAGE containing 0.1% casein was soaked in 2.5% (v/v) Triton X-100 at room temperature for 1 hour followed by overnight incubation in 50 mM Tris buffer (pH 8).…”
Section: Zymogram Analysismentioning
confidence: 99%
“…The activity of proteases in gel was detected using casein zymography (Bester et al, 2010). After electrophoresis, SDS-PAGE containing 0.1% casein was soaked in 2.5% (v/v) Triton X-100 at room temperature for 1 hour followed by overnight incubation in 50 mM Tris buffer (pH 8).…”
Section: Zymogram Analysismentioning
confidence: 99%
“…A significant increase in cGMP levels was observed during the ischemic period. Bester et al (2010) have shown that a dietary intake of 7 mg kg À1 RPO could reduce infarct size. These findings suggest that RPO can also protect the heart in the ischemic period, but rather through a different mechanism involving NO-cGMP.…”
Section: Involvement Of the No-cgmp Pathway And Mmp In Red Palm Oil Pmentioning
confidence: 99%
“…Initially, all studies by the Van Rooyen group (Bester et al, , 2010Engelbrecht et al, 2006;Esterhuyse et al, 2006;Kruger et al, 2007) on red palm oil supplementation in the ischemia/ reperfusion anoxic model were performed using a daily dose of 7 mg kg À1 diet in the rat model. Initially, all studies by the Van Rooyen group (Bester et al, , 2010Engelbrecht et al, 2006;Esterhuyse et al, 2006;Kruger et al, 2007) on red palm oil supplementation in the ischemia/ reperfusion anoxic model were performed using a daily dose of 7 mg kg À1 diet in the rat model.…”
Section: Optimal Feeding Period and Dosage Of Red Palm Oil To Offer Pmentioning
confidence: 99%
“…We put the sliced hearts in TTC with the concentration of 1% to be incubated for 15 minutes and we turned over the hearts once in this process. When the TTC staining was over, the heart slices were dried with filter paper, and then these slices were covered in formalin solution for 15 minutes, Finally, these Journal of Chemistry 3 slices were immersed in phosphate buffer at 4 ∘ C (pH 7.4) [16]. Heart slices were digitally imaged using a Canon camera.…”
Section: Evaluation Of Myocardial Infarctmentioning
confidence: 99%